Standardization of molecular genetic techniques for the characterization of germplasm collections: The case of random amplified polymorphic DNA (RAPD) - Lowe, A.J.; Hanotte, Olivier H.; Guarino, Luigi (1996)
Random amplified polymorphic DNA (RAPD) variation is being used increasingly to characterize germplasm collections. However, the technique has limitations due to the lack of reproducibility of results under certain conditions. Here we review some of the literature on the factors that are mainly responsible for variation in the generation of RAPD fragments, and examine ways to reduce these sources of unwanted variation. We propose a table containing a collation of all the descriptors thought necessary to describe the conditions and assessment procedures necessary for reproducible RAPD profiling of plant material. The standardization of procedure and presentation of results should facilitate the comparison of results both between and within laboratories working on similar material, and allow RAPDs to be used as a standard germplasm descriptor.